ANALISIS ALOKASI DANA DESA DALAM PEMBANGUNAN EKONOMI PERSPEKTIF IBNU KHALDUN - Munawar, Rizal; Nursyafika, Nursyafika; Lasmi, Lasmi; Nurhalifah, Nurhalifah; Naimah, Naimah; Ameliah, Nur Cahya (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
This research aims to reveal how the village fund budget (ADD) is allocated in the economic development process from Ibn Khaldun's perspective. with special emphasis on how this concept can be applied at the village level, especially in Bima district. In his work "Muqaddimah", Ibn Khaldun introduced important theories such as the role of humans or ar-rijal, the role of development and justice, the role of institutions and government, and the role of wealth or al-mal, which provides in-depth information about social, political and economic dynamics. involved in the development of civilization. The research method used was a qualitative approach, and data was collected through interviews, observation, literature study, and document analysis relating to village fund budget policies in Bima district. Research shows that using Ibn Khaldun's theory in the distribution and use of village budgets can increase local economic development by utilizing social solidarity, strengthening local leadership, and ensuring that wealth is distributed fairly. This study can increase our understanding of classical theory in modern economic development, especially in rural areas. It is hoped that this research can help policy makers create sustainable and fair development strategies.